Dielectric resonator-based two-port filtennas with pattern and space diversity for 5G IoT applications. Issue 2 (7th March 2023) - Sharma, Darshika; Katiyar, Rishika; Dwivedi, Ajay Kumar; Nagesh, K.N.; Sharma, Anand; Ranjan, Pinku
Abstract: This paper describes a multiple-input multiple-output (MIMO) antenna for low millimeter (mm)-wave applications based on dielectric resonators. This is the first time that a filtering response is used in conjunction with an MIMO antenna operating at a low mm-wave frequency. The antenna is simulated using an asymmetrical U-shaped aperture and a microstrip line feed. The suggested filtenna has two distinguishing characteristics: (i) the diversity parameters of the proposed MIMO are increased by including pattern and spatial diversity, and (ii) the proposed feed mechanism of a dielectric resonator provides the filtering response. Between the two ports, a metallic plate tilts the radiation pattern by 45°. The anti-parallel locations of the ports increase the isolation value by >30 dB. To validate the performance of the suggested antenna, the proposed filtenna was built and confirmed. The proposed antenna operates between the frequencies 27.9 and 28.5 GHz. Within the operating frequency range, the observed gain is ~4.5 dBi. On the contrary, the gain suppression level beyond the operational frequency range is ~15 dB. The stable radiation properties and high diversity parameter values of the suggested filtenna make it an effective solution for 5G Internet of Things sensing applications.